Differences in the salivary flow rate, buffer capacity, and pH, based on the length of inhalants usage in bronchial asthma patients - Sinaga, Naomi Tio Agustine; Wihardja, Rosilawati; Sari, Kartika Indah (Padjadjaran Journal of Dentistry, 2022)
Introduction: Asthma or bronchial asthma is a chronic respiratory tract inflammation process involving many cells, including their elements, and can cause severe and plentiful responses from the respiratory tract. Administration of inhalation drugs is the primary medication in treating bronchial asthma. Inhalants are given appropriately with dosage and usage period based on the severity level of bronchial asthma. This research aimed to analyse the differences in the salivary flow rate, buffer, and pH, based on the length of inhalants usage in bronchial asthma patients. Methods: The research was descriptive-comparative involving 40 bronchial asthma patients (6 male and 34 female) from the Community Lung Health Center of Bandung, taken as samples using the central theorem limit sampling method. The subjects were ordered to collect their saliva in the saliva collection cups with a draining method. Then, the salivary flow rate, buffer, and pH were examined. Data distribution was tested, resulting in normally distributed data; thus, a parametric independent t-test with a significant level of 0.05 was applied. Results: Subjects in the group of inhalant usage for more than ten years had low and very low categories of salivary flow rate, buffer, and pH. There were significant differences in the salivary flow rate, buffer, and pH of the bronchial asthma patients based on their length of inhalants usage (1-5 years; >5 years–10 years; >10 years; p<0.05). Conclusions: There are differences in the salivary flow rate, buffer, and pH based on the length of inhalants usage in bronchial asthma patients. The longer the usage period, the lower the salivary flow rate, buffer, and pH.